Inclusive Growth in Indonesia: An Environmental Sustainability Approach - Ahmad Soleh; Kresnawati Kresnawati; Andy Mulyana; Made Setini; Heru Wahyudi (UNIVED Press, 2025)
This study aims to analyse inclusive growth in Indonesia using an environmental sustainability approach. The approach used in this research is descriptive analysis. The data collection technique used a literature study. The data used is secondary data sourced from books, journals, reports and official information from BPS-Statistics Indonesia. Poverty-Equivalent Growth Rate (PEGR) is a method developed to measure the inclusive growth coefficient in Indonesia. The measurement of inclusive growth has mostly been done using poverty, income distribution inequality and employment approaches. This study introduces a new concept in measuring the inclusiveness of economic growth using the environmental sustainability approach. The results showed that during the period 2001-2022 Indonesia's economic growth has not been inclusive. The inclusive growth coefficient (IGen) is smaller than the economic growth coefficient (Ĝg). This phenomenon occurred in most provinces and islands during the observation period. High economic growth has not been accompanied by environmental sustainability. Increased population growth and high economic activity contribute to environmental degradation. Government strategies and policies are needed as well as the commitment of various parties for sustainable development.